A novel geothermal combined cooling and power cycle based on the absorption power cycle: Energy, exergy and exergoeconomic analysis. (15th June 2018) - Parikhani, Towhid; Ghaebi, Hadi; Rostamzadeh, Hadi
Abstract: Energy, exergy, and exergoeconomic analysis of a novel combined cooling and power (CCP) system for producing cooling and power outputs are presented based on the absorption power cycle (APC), using geothermal energy as low-temperature heat source. A comprehensive thermodynamic modeling of the proposed CCP system is carried out leading to determine the main source of irreversibility and performance characteristics of the system for a better thermal design purpose. In the parametric study, the effect of key thermodynamic parameters (i.e., generator hot pinch point temperature difference (PPTD), generator cold PPTD, ammonia concentration, absorber minimum temperature difference, condenser minimum temperature difference, evaporator temperature, and geothermal temperature) on the key performance parameters (i.e., net output power, cooling capacity, thermal efficiency, exergy efficiency, and sum unit cost of product (SUCP) of system) are investigated. It is found that the proposed system can produce cooling capacity and net output power of 221.4 kW and 161.2 kW, respectively, under supplying 2333 kW heat from the geothermal source. In this case, the overall thermal efficiency, exergy efficiency, and SUCP of system are calculated by 16.4%, 28.95% and 93.87 $/GJ, respectively. From exergy analysis it is understood that among all components, absorber accounted for the largest contribution of exergy destruction which constituted around 39.89% of the overall exergy destruction of system. In addition, the highest cost of exergy destruction corresponded to the absorber which is followed by the condenser. Finally, parametric study revealed that the exergy efficiency of the proposed system can be maximized based upon the ammonia concentration and evaporator temperature. Moreover, it is shown that the thermal efficiency of system can be increased by increasing of the generator hot PPTD and evaporator temperature or decreasing ammonia concentration, absorber and condenser minimum temperature differences, and geothermal temperature. While, it is also found that the SUCP of system can be decreased by increasing the generator cold PPTD, condenser minimum temperature difference, and geothermal temperature or decreasing the generator hot PPTD, absorber minimum temperature difference, and evaporator temperature. Highlights: A novel geothermal cogeneration system for producing cooling and power is proposed. Energy, exergy and exergoeconomic assessments of the proposed cogeneration system are carried out. Comprehensive parametric study of some key thermodynamic parameters on performance criteria is performed.